The maiden king the reunion of masculine and feminine - Bly, Robert 1926-2021; Woodman, Marion 1928- (Holt, 1998)
In The Maiden King, two wise teachers guide us through the rich, metaphorical world of an ancient folktale to explore the possibility of a new relationship between masculine and feminine. Here, both women and men will find a vision of the powerful feminine, an energy our contemporary world has not been able to receive or sustain. This book presents a map of the sorrow both men and women feel today in relation to each other, and it provides a guide to their eventual reconciliation. The steps of reunion are not laid out in sociological language, but rather in the ancient language of metaphor, which retains an astonishing color and vividness. Ultimately, by the end of The Maiden King, both masculine and feminine find a place of intersection where they can discard their false projections of each other.
Keywords: Jung, C. G <1875-1961> -- (Carl Gustav); Interpretatie; Rusland; Sekseverschillen; Sprookjes; Geschlechtsunterschied; Femininity; Maiden Tsar (Tale); Masculinity; Psychoanalysis and folklore; Tales -- Russia (Federation) -- History and criticism; Russisch; Männlichkeit; Erzählung; Weiblichkeit